The Influence of Dengue Fever in the working area of UPTD puskesmas Cigandamekar Kuningan Regency in 2024 - Amelia Chandra Sari Dewi Ratna Suminar (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the factors influencing the rising cases of dengue fever in the working area of UPTD Puskesmas Cigandamekar Kuningan in 2024. The research employed a descriptive qualitative approach with data collection through structured interviews, observations, and document review from 2023 to 2024. The data were analyzed thematically to identify key contributing factors, including community knowledge, environmental sanitation, and healthcare access. The results indicate that low community awareness of prevention, poor sanitation conditions, and the lack of sustainable health programs are primary factors behind the increase in cases. The study concludes that enhancing community education, improving environmental management, and encouraging active community participation are essential for effective dengue prevention. It recommends an integrated and sustainable approach to control disease transmission and improve public health outcomes.